Dynamic characteristic simulation of hydraulically damped rubber mount based on finite element parameter estimation for vehicle powertrain. (2nd April 2009) - Wang, L.R.; Lu, Z.H.; Hagiwara, I.
Performance analysis of the dynamic characteristics of hydraulically damped rubber mounts (HDM) faces challenges owing to the fluid-structure interaction between rubber springs and fluid in chambers, non-linear material properties of rubber parts and turbulent flow in chambers and fluid track linking chambers. In this article, finite element-based parameter estimation and lumped-parameter modelling of HDM are developed for numerical simulation of dynamic characteristic of HDM. Dynamic characteristics of a typical HDM with fixed decoupler are predicted and compared with experimental results, which verify the effectiveness of the proposed approach. The presented approach provides design guidelines for HDM to meet vibration isolation requirements of a powertrain mount system through parameter adjustment.